2012
DOI: 10.5588/ijtld.11.0121
|View full text |Cite
|
Sign up to set email alerts
|

Increasing directly observed therapy related to improved tuberculosis treatment outcomes in Taiwan

Abstract: These findings highlight the importance of ensuring universal DOT in improving treatment outcomes among new pulmonary TB patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 0 publications
3
9
2
Order By: Relevance
“…In this study, smear positive PTB was found to be associated with poor treatment outcome as previously reported [23]. In contrast to our finding, however, some studies [8,19] reported that having smear positive PTB is associated with favorable treatment outcomes.…”
Section: Discussionsupporting
confidence: 62%
“…In this study, smear positive PTB was found to be associated with poor treatment outcome as previously reported [23]. In contrast to our finding, however, some studies [8,19] reported that having smear positive PTB is associated with favorable treatment outcomes.…”
Section: Discussionsupporting
confidence: 62%
“…The default rate (4.9%) encompassed the foremost part of the unsuccessful outcome and was higher than that (0.6-3.8%) reported from other regions (Hailu, Abegaz & Belay, 2014;Satyanarayana et al, 2010;Tilahun & Gebre-Selassie, 2016) but lower (7%) than that informed by Aketi et al, 2016. In multivariate analysis, rural areas, sputum smear positivity, underweight, and retreatment were significantly associated with poor treatment outcomes. These findings are in line with previous studies (Bloss et al, 2012;Jaganath & Mupere, 2012;Sharma et al, 2008). The most important reason for all these risk factors could be non-adherence due to lack of education among the caregivers.…”
Section: Discussionsupporting
confidence: 94%
“…One of the possible reasons for this is the high percentage (129/134, 96.3%) of directly observed therapy (DOT). The CDC of Taiwan has enforced the DOT program since 2006, and the implementation rate of DOT for TB case now exceeds 90% [16]. In Taiwan, once a TB case is verified, the patient is invited to participate in the DOT program.…”
Section: Discussionmentioning
confidence: 99%